Socio-Environmental Conflicts in Southern Chile. Actors, Power Mechanisms and Influence on the Challenge of Reducing Rural Poverty [Conflictos Socioambientales en el Sur de Chile. Actores, Mecanismos de Poder E Incidencia Para Disminuir la Pobreza Rural] - Zorondo-Rodriguez, F (CEDDAR, 2022)
Chile has made vast strides in terms of the reducing of poverty. However, some rural areas of the country display persistent indicators of backwardness and poverty. Socio-environmental conflicts and their impact on residents well-being are among the defining characteristics of these territories. Based on interviews with key actors associated with 30 rural territories in southern Chile, this study identifies 34 socio-environmental conflicts which are perceived as the main causes of socio-territorial inequalities and analyzes the mechanisms of influence that actors deploy in them. Thirty-two types of conflicts have an anthropological origin whereas that two of them are natural phenomena locally perceived as conflicts. Most of the conflicts with anthropological origin are related to loss of environmental assets. If environmental conflicts are the cause and effect of poverty tramps and territorial inequalities, then the management of such assets emerges as a major element in strategies aimed at poverty. The conflicts identified mostly derive from extractive, high-entropy economic activities that have formed the historical basis of the economic model in the area studied. It is concluded that environmental assets and territory management policies must be developed considering a revision of political-institutional arrangements and new governance models. © 2022, CEDDAR. All rights reserved.